2012
DOI: 10.15353/joci.v8i1.3058
|View full text |Cite
|
Sign up to set email alerts
|

Can The Nintendo Wii(tm) Sports Game System Be Effectively Utilized In The Nursing Home Environment: A Feasibility Study?

Abstract: This mixed-method study examined the feasibility and potential benefits of five weeks of Nintendo Wii SportsTM (NWS) play for 11 nursing home residents. Nursing home staff and residents suggested that the NWS is feasible in the nursing home context and that it has psychosocial benefits. While no significant changes in dynamic stability, health-related quality of life (QOL) or fear of falling were observed (p = 0.185-0.841), a moderate effect size for physical health-related QOL was found. Randomized controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Two studies did not provide fixed exergaming sessions to the residents, instead they were free to play if and when they wanted. This resulted in a similar amount of mean playing time, i.e., 28 min per week over 5 weeks ( Keogh et al, 2012 ) and 30 min per week over 8 weeks ( Keogh et al, 2014 ), respectively. In both studies, the mean duration was consistent across the course of the intervention.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies did not provide fixed exergaming sessions to the residents, instead they were free to play if and when they wanted. This resulted in a similar amount of mean playing time, i.e., 28 min per week over 5 weeks ( Keogh et al, 2012 ) and 30 min per week over 8 weeks ( Keogh et al, 2014 ), respectively. In both studies, the mean duration was consistent across the course of the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…From the additional search, another 75 articles were included in the full-text screening, of which 8 met the inclusion criteria. Thus, a total of 28 articles were included in this systematic review ( Chan et al, 2001 ; Brandt and Paniagua, 2011 ; Keogh et al, 2012 ; Pichierri et al, 2012 ; Ulbrecht et al, 2012 ; Janssen et al, 2013 ; Keogh et al, 2014 ; Fu et al, 2015 ; Grigorova-Petrova et al, 2015 ; Rogan et al, 2016 ; Yesilyaprak et al, 2016 ; Delbroek et al, 2017 ; Monteiro-Junior et al, 2017 ; Hutchinson et al, 2018 ; Kamińska et al, 2018 ; Sun et al, 2018 ; Taylor et al, 2018 ; Wu et al, 2019 ; de Bruin et al, 2020 ; Cicek et al, 2020 ; Fakhro et al, 2020 ; Rica et al, 2020 ; Babadi and Daneshmandi, 2021 ; Huang et al, 2021 ; Loggia et al, 2021 ; Marinus et al, 2021 ; Ramnath et al, 2021 ; Zahedian-Nasab et al, 2021 ). The PRISMA flow diagram of the study selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations